Integrating Qur’anic Values into Holistic Character Development in Early Childhood Education: A Conceptual Play-Based Framework - Abdur Raqib; M. Tamrin; Zakiyatul Mutiah; Widodo Fariz; Imam Hambali; Siti Farhah A. Aziz (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2026)
Early childhood education (ECE) requires a solid value foundation to ensure that children’s character formation, self-regulation, and social–emotional development evolve holistically and sustainably. However, studies in early childhood education and Qur’anic values are often treated as separate domains and have not yet been conceptually integrated within a developmentally appropriate pedagogical framework. This research aims to analyze the values of children’s education in QS. Luqmān (31): 13–18 based on Tafsīr al-Qurṭubī and formulating a conceptual model of early childhood character development that is in line with the principles of developmentally appropriate practice and play-based learning. This study uses a qualitative approach, with a literature research design and a thematic-conceptual interpretation analysis. The subject of the research is in the form of a QS text. Luqmān (31): 13–18 in Tafsīr al-Qurṭubī, supported by early childhood literature and contemporary character education. Data is analyzed through deep Reading, thematic coding, and conceptual interpretation. The results of the study show that Qur’anic values form an integrated structure of children’s character, including spiritual orientation, moral affection, self-regulation, social responsibility, and communication ethics. These findings have implications for the development of early childhood character education based on habituation, example, and meaningful play experience. This study concludes that Qur’anic values are relevant as the conceptual basis for holistic and contextual early childhood character education.